Reflections from “Revisioning Feminist Engagements with Madness”: Borderline, Futurity, and Debility - Tichenor, Erin (Atlantis)

(untitled) (Mount Saint Vincent University, 2024)
This commentary builds on my presentation in the panel “Revisioning Feminist Engagements with Madness” at the 2023 Women’s, Gender, and Social Justice annual conference. In doing so, this piece grapples with several debates surrounding the stigmatized psychiatric label of “borderline personality disorder (BPD).” While feminists have long called for the diagnosis to be removed or replaced, Mad-affirmative scholars are reconceptualizing borderline as a cluster of insightful experiences and psychocentric activists are trying to destigmatize and raise awareness about “BPD.” The latter two efforts are very different from each other, yet both seem to be located in white, globally elite spaces. This piece suggests that we can learn from other reclamation movements that, co-opted by the colonial state and neoliberal market, have mainly benefited elites, and thus cautions against any attempt to universally reclaim, reject, or reconceptualize borderline. That is, rather than unpacking what borderline really is or should mean, this piece asks what borderline does, for whom, in which contexts, and towards what ends. Drawing from Gilles Deleuze’s ethological method and Jasbir Puar’s work on debility and capacity, this article acknowledges the socio-political patterns of borderline, as well as the broader systems we might be serving in our seemingly progressive discourses.